1996
DOI: 10.1016/s0092-8674(00)81233-7
|View full text |Cite
|
Sign up to set email alerts
|

trp, a Novel Mammalian Gene Family Essential for Agonist-Activated Capacitative Ca2+ Entry

Abstract: Capacitative calcium entry (CCE) describes CA2+ influx into cells that replenishes CA2+ stores emptied through the action of IP3 and other agents. It is an essential component of cellular responses to many hormones and growth factors. The molecular basis of this form of Ca2+ entry is complex and may involve more than one type of channel. Studies on visual signal transduction in Drosophila led to the hypothesis that a protein encoded in trp may be a component of CCE channels. We reported the existence of six tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
559
3

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 638 publications
(579 citation statements)
references
References 60 publications
17
559
3
Order By: Relevance
“…(i) The Drosophila melanogaster trp gene product has a similar sequence to the cq subunit of the L-type Ca 2+ channel, but lacks charged residues in the $4 segment [10], the part of the cxl subunit that is thought to sense a change in voltage [17]. Transfection of mammalian trp gene homologues in a mammalian cell line (COS-M6) enhanced store-operated Ca 2+ entry beyond that found in nontransfected cells, while transfection of mouse fibroblast L-cells with antisense cDNA fragments of murine trp homologues resulted in the abolition of store-operated Ca 2+ influx [18]. This indicates that mammalian trp gene homologues encode proteins that can participate in store-operated Ca 2+ entry in non-excitable mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…(i) The Drosophila melanogaster trp gene product has a similar sequence to the cq subunit of the L-type Ca 2+ channel, but lacks charged residues in the $4 segment [10], the part of the cxl subunit that is thought to sense a change in voltage [17]. Transfection of mammalian trp gene homologues in a mammalian cell line (COS-M6) enhanced store-operated Ca 2+ entry beyond that found in nontransfected cells, while transfection of mouse fibroblast L-cells with antisense cDNA fragments of murine trp homologues resulted in the abolition of store-operated Ca 2+ influx [18]. This indicates that mammalian trp gene homologues encode proteins that can participate in store-operated Ca 2+ entry in non-excitable mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specificity of the antibody was confirmed using in vitro translation products prepared with cDNAs for mTRPC2 clone 14 (24), mTRPC2 clone 17 (24), and mTRPC6 (28), cloned into pcDNA3. The in vitro products were prepared with the TNT quick coupled transcription/translation system (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…A vast number of papers have reported that many TRPC channels function as SOC. Zhu et al (7) first reported that expression of human TRPC3 in cultured human embryonic kidney (HEK) cells gives rise to agonist-and thapsigargin-activated channel activity. Because thapsigargin depletes intracellular Ca 2ϩ stores by inhibiting the endoplasmic reticulum Ca 2ϩ -ATPase, the authors concluded that TRPC3 proteins constitute subunits of SOC.…”
Section: Role Of Trp In Plc-dependent Ca 2ϩ Influxmentioning
confidence: 99%